The effect of hands-on activity and problem-based learning on achievement of biology students in Enugu state - Nwankwo, Amaka Loretta; Ugwu, Theresa Ukamaka; Ukala, Geoffrey; Benson, Ozichi Okwukwe (Inornatus: Biology Education Journal, 2024)
The research researched the impact of problem-based learning and hands-on activity on the students' academic performance in biology. The study implemented a quasi-experimental design, specifically a non-equivalent control group design with a pre-and post-test design. The study's population consisted of 2691 students from 32 public secondary schools in the Nsukka. We used a multi-stage sampling procedure to sample 85 SS II students from two intact classes. The researchers developed the "Biology Achievement Test (BAT)" as an instrument for data collection. We used the mean and standard deviation to answer the research question and used the ANCOVA to test the null hypotheses. The study's findings revealed that there is a significant difference in the mean achievement scores of secondary school students taught biology using the hand-on activity method and problem-based learning. According to the study, biology teachers should always use hands-on activities when teaching biology to students. Based on the findings, we recommend training biology teachers through workshops, orientation courses, and seminars on adopting hands-on activities in teaching to enhance students' academic achievement in biology. The study concluded that using hands-on activities in teaching biology is more effective in enhancing students' biology achievement.